Challenging patents: third party observations - Atkinson, Jonathan D.M. (Henry Stewart Talks, 2021)
How to challenge a third party’s patent at the European Patent Office, Introduction to criteria for patent to be granted, Legal basis for challenging a patent application – third party observations, How Third Party Observations are filed, Why Third Party Observations are important